A Light‐Responsive Metal–Organic Framework Hybrid Membrane with High On/Off Photoswitchable Proton Conductivity. (13th March 2020) - Liang, Hong‐Qing; Guo, Yi; Shi, Yanshu; Peng, Xinsheng; Liang, Bin; Chen, Banglin
Abstract: Mimicking biological proton pumps to achieve stimuli‐responsive protonic solids has long been of great interest for their diverse applications in fuel cells, chemical sensors, and bio‐electronic devices. Now, dynamic light‐responsive metal–organic framework hybrid membranes can be obtained by in situ encapsulation of photoactive molecules (sulfonated spiropyran, SSP), as the molecular valve, into the cavities of the host ZIF‐8. The configuration of SSP can be changed and switched reversibly in response to light, generating different mobile acidic protons and thus high on/off photoswitchable proton conductivity in the hybrid membranes and device. This device exhibits a high proton conductivity, fast response time, and extremely large on/off ratio upon visible‐light irradiation. This approach might provide a platform for creating emerging smart protonic solids with potential applications in the remote‐controllable chemical sensors or proton‐conducting field‐effect transistors. Abstract : Protonengesteuerter Dimmer : Lichtregulierte Protonenleitung in MOF‐Membranen wurde durch In‐situ‐Einkapselung lichtaktiver Moleküle in 3D‐Gerüste erreicht. Die Hybridmembran hat eine hohe Protonenleitfähigkeit und herausragende Eigenschaften als Schalter, wodurch es möglich wird, die Helligkeit einer LED‐Lampe zu kontrollieren, die in einen optisch kontrollierten Schaltkreis eingebaut wurde.